Effect of baking in different ovens on the quality and structural characteristics of saltine crackers. (4th October 2021) - Saberi, Farzad; Kouhsari, Fatemeh; Abbasi, Samaneh; Rosell, Cristina M.; Amini, Mehdi
Summary: The aim of the study was to evaluate the physical and microstructural characteristics of crackers baked in four different industrial baking ovens (indirect radiation‐cyclotherm, indirect convection, hybrid and industrial tunnel‐ITO). Indirect convection and cyclotherm ovens provide the highest (5685.43 ± 51 W m −2 ) and the lowest (4860 ± 38.87 W m −2 ) amount of heat flux, respectively. Despite the amount of heat flux, indirect convection led to crackers with the highest moisture (7.86% vs. 4.82% in clyclotherm) and specific volume, but the lowest hardness. Cyclotherm resulted in crackers with lower specific volume, surface area, porosity, smooth and regular surface. Conversely, the hybrid and ITO ovens showed closer heat flux, leading to crackers with similar moisture content, texture parameters, specific volume, browning and inner porosity. Overall results show the potential of baking using different ovens for modifying the quality parameters of the crackers. Abstract : Impact of oven type on crackers structure